Land Issues in Forest Areas of Yogyakarta Special Region and The Dynamic of Decision Making Process - Soraya Isfandiari; Ambar Widaningrum; Nunuk Dwi Retnandari (Policy & Governance Review, 2020)
There is a forest land identified as Ab Gronden, located in Gunung Kidul Regency, Yogyakarta Special Region. Ab Gronden occupation has led to prolonged conflict over land until today. Environment and Forestry Service (EFS) of Yogyakarta Special Region has made a decision of “do nothing” from the policy set by central government to solve the problem. This study intends to examine factors underlying the decision of “do nothing". This type of research is a case study, that is a study on a policy in the context of real life and uses historical approach holistic single case study through the procedures of data collection and analysis systematically. The sources of data in this study consisted of both primary and secondary sources of data and were analyzed qualitatively. The results of this study found the following conclusion factors underlying of why decision of “do nothing” choosed by EFS is because of there is no policy agenda of forest land statue yet. EFS has experience a dilemma and conflict to make a decision relate to: a) the differences in the ab gronden perception among actors, b) multy level hierarchy of decision making, c) there is no initiation of dialogue between related actors. The Organizational Politics Model has not been able to work in decision making of government organizations that are grounded in legal provisions. The do nothing decision was made because the bargaining process between the actors was not running.